2014
DOI: 10.1039/c4py01002g
|View full text |Cite
|
Sign up to set email alerts
|

Thermally cleavable imine base/isocyanate adducts and oligomers suitable as initiators for radical homo- and copolymerization

Abstract: Adducts and oligomers of imines and isocyanates are promising candidates as meta-stable isocyanate blockers and latent telomeric block-copolymer sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…However, the case of TMG is particular since its bears a labile hydrogen atom (in fact, Cy 2 MeBuG also has one, but it is a secondary-conjugated amine and this proton should not be very reactive toward isocyanates or should only lead to an equilibrium). TMG can therefore easily react with the diisocyanate IPDI to yield a stable adduct (note that other guanidines, not bearing labile protons, are also susceptible to yield 2:1 adducts with a heterocyclic triazinedione moiety, but this was not observed for the case of IPDI and tBuTMG because of steric hindrance [41]). Apart from consuming a slight amount (1% at the most) of isocyanate functions, the formation of the IPDI-TMG adduct could also participate in the catalytic activation.…”
Section: New Guanidine Derivatives As Catalystsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the case of TMG is particular since its bears a labile hydrogen atom (in fact, Cy 2 MeBuG also has one, but it is a secondary-conjugated amine and this proton should not be very reactive toward isocyanates or should only lead to an equilibrium). TMG can therefore easily react with the diisocyanate IPDI to yield a stable adduct (note that other guanidines, not bearing labile protons, are also susceptible to yield 2:1 adducts with a heterocyclic triazinedione moiety, but this was not observed for the case of IPDI and tBuTMG because of steric hindrance [41]). Apart from consuming a slight amount (1% at the most) of isocyanate functions, the formation of the IPDI-TMG adduct could also participate in the catalytic activation.…”
Section: New Guanidine Derivatives As Catalystsmentioning
confidence: 92%
“…Guanidines and amidines have indeed been mentioned as blocking agents for isocyanates, but this remains rather occasional. [41,43,44] Moreover, a comparison between Figures 4 and 5 suggests that the adduct has in fact rather similar effects on the kinetics at the beginning of the reaction, although the conditions are different (0.1 mol%, 60 °C vs. 1 mol%, 80 °C). But the final conversions are nevertheless very different since x NCO almost stops increasing after about 3 h in the first case, whereas it keeps on increasing to reach 0.5 and above in the second case.…”
Section: New Guanidine Derivatives As Catalystsmentioning
confidence: 93%
“…Cyclic amidines can react with heterocumulenes such as carbon dioxide and carbon disulfide to form zwitterionic compounds because they exhibit high nucleophilicity and because the generated zwitterions can delocalize on the amidine ring . In the case of other heterocumulene derivatives (e.g., isocyanate, isothiocyanate, and carbodiimide), no research has been reported except zwitterion formation by 1:2 cyclotrimerization of cyclic amidines and isocyanates . The development of polymerizable zwitterionic compounds necessitates the design and synthesis of new zwitterions.…”
Section: Introductionmentioning
confidence: 99%
“…Isocyanates are also of great importance for new conceptions in polymer chemistry. Recently, isocyanates in conjunction with imine compounds have been proved as an innovative source for new polymer synthesis strategies . Imines are organic molecules that contain a carbon–nitrogen double bond (CRN) such as, amidines, guanidines, azines, and azomethines.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, diisocyanates are able to undergo crisscross addition polymerization with azines resulting in N ‐heterocycle containing polymers (Scheme ) . Related polymer structures, which contain cyclic triazinedione repeating moieties, are available from 1,8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) or other appropriate imine bases (Scheme ) . Both types of polyaddition reactions as well as the radical formations of isocyanates with imine bases obviously proceed via zwitterionic intermediates …”
Section: Introductionmentioning
confidence: 99%